Blood metabolites as mediators in erectile dysfunction: insights from a multi-center proteomics and genetic study - Chen, Junhao; Zhao, Junxian; Zhang, Zhi; Zhu, Xingcheng; Zuo, Jieming; Nie, Zuqing; Fu, Yuanzhi; Wang, Haifeng; Tang, Mengjun; Fu, Shi (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to identify circulating proteins causally associated with erectile dysfunction (ED) using Mendelian randomization (MR) analysis.MethodsWe utilized two of the largest multi-center proteomics databases as exposures and the FinnGen database as the outcome source. A large-scale two-sample MR analysis, including coloc colocalization analysis and SMR (Summary data-based Mendelian Randomization) analysis, was conducted to evaluate the reliability of proteomic effects on ED outcomes. Additionally, MR mediation analysis involving 1,400 blood metabolites was performed to investigate how these proteins mediate the effect of blood metabolites on ED. Finally, protein-protein interaction analysis, pathway enrichment analysis, druggability assessments, and molecular docking were employed to further elucidate the mechanisms of ED and identify potential therapeutic targets.ResultsEight circulating proteins (AMN, ESM1, KIR2DL2, PIGR, SPINT1, SPP1, TNFRSF6B, TMEM9) were identified as causally associated with ED based on two-sample MR and coloc colocalization criteria. Among these, five proteins (AMN, ESM1, KIR2DL2, PIGR, TNFRSF6B) satisfied SMR validation, while SPINT1, TMEM9, and SPP1 were excluded. Several of these proteins were found to mediate the relationship between metabolites and ED. These proteins are recognized as either druggable targets or existing drug targets, with molecular docking results demonstrating favorable interactions with various drug candidates.ConclusionUsing MR analysis, we identified five proteins associated with ED, clarified protein-mediated mechanisms, and proposed promising therapeutic targets for ED.